Enhancing Eco-efficiency in Agro-ecosystems through Soil Carbon Sequestration - Lal, R. (Wiley, 2010)
Global cereal production must be increased by ∼50% by 2050. Crop yields in sub‐Saharan Africa and South Asia have either stagnated or declined since the 1990s because of the widespread use of extractive farming practices and problems of soil and environmental degradation. Yield potential of improved varieties and elite germplasm is not realized because of soil degradation. The concept of eco‐efficiency implies efficient and sustainable use of resources in agronomic production and soil management. However, it is not enough to merely minimize the environmental impact. It is also important to maximize agronomic production while enhancing ecosystem services. Most degraded and depleted soils of agro‐ecosystems contain a lower soil organic carbon (SOC) pool than in those under natural ecosystems. Thus, restoring the SOC pool is essential to improving soil quality, increasing eco‐efficiency, and enhancing numerous ecosystem services. Increasing the SOC pool in the root zone can enhance agronomic production (kg grains ha−1 Mg C−1) at the rate of 200 to 300 for maize (Zea mays L.), 30 to 60 for bean (Phaseolis vulgaris L.), 20 to 40 for wheat (Triticum aestivum L.), 20 to 50 for soybean [Glycine max (L.) Merr.], and 20 to 50 for rice (Oryza sativa L.). Not all improved management practices are applicable to all soil and ecological conditions. However, no‐till farming along with application of crop residue mulch, manuring, legume‐based complex rotations, and integrated nutrient management should be applicable under most conditions. Global food insecurity, affecting 1.02 billion people in 2009, can only be alleviated by improving soil quality and eco‐efficiency through restoration of degraded/depleted soils.